Saving lives with public access defibrillation: A deadly game of hide and seek. (July 2018) - Sidebottom, David B.; Potter, Ryan; Newitt, Laura K.; Hodgetts, Gillian A.; Deakin, Charles D.
Abstract: Background: Early defibrillation is a critical link in the chain of survival. Public access defibrillation (PAD) programmes utilising automated external defibrillators (AEDs) aim to decrease the time-to-first-shock, and improve survival from out-of-hospital cardiac arrest. Effective use of PADs requires rapid location of the device, facilitated by adequate signage. We aimed to therefore assess the quality of signage for PADs in the community. Method: From April 2017 to January 2018 we surveyed community PADs available for public use on the 'Save a Life' AED locator mobile application in and around Southampton, UK. Location and signage characteristics were collected, and the distance from the furthest sign to the AED was measured. Results: Researchers evaluated 201 separate PADs. All devices visited were included in the final analysis. No signage at all was present for 135 (67.2%) devices. Only 15/201 (7.5%) AEDs had signage at a distance from AED itself. In only 5 of these cases (2.5%) was signage mounted more than 5.0 m from the AED. When signage was present, 46 used 2008 ILCOR signage and 15 used 2006 Resuscitation Council (UK) signage. Signage visibility was partially or severely obstructed at 27/66 (40.9%) sites. None of the 45 GP surgeries surveyed used exterior signage or an exterior 24/7 access box. Conclusions: Current signage of PADs is poor and limits the device effectiveness by impeding public awareness and location of AEDs. Recommendations should promote visible signage within the operational radius of each AED.